Primary Aldosteronism and Ischemic Heart Disease - Patil, Shivaraj; Rojulpote, Chaitanya; Amanullah, Aman (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease, in particular ischemic heart disease is a major cause of morbidity and mortality worldwide. Primary aldosteronism is the leading cause of secondary hypertension, yet commonly under diagnosed, and represents a major preventable risk factor. In contrast to historical teaching, recent studies have shown that excess aldosterone production is associated with increased burden of ischemic heart disease disproportionate to the effects caused by hypertension alone. Aldosterone through its genomic and non-genomic actions exerts various detrimental cardiovascular changes contributing to this elevated risk. Recognition of primary hyperaldosteronism and understanding the distinctive pathophysiology of ischemic heart disease in primary aldosteronism is crucial to develop strategies to improve outcomes.